Piezoelectric Transformer of Travelling Wave Type. - Schulte, Thomas; Kauczor, Christopher; Grotstollen, Horst (ACTUATOR 2004)
Varios desings of piezoelectric transformers are know, but due to the limitation of a finite miechanical structure only standing wave excitation in used up to now. This paper outlines a novel concept based on a travelling wave instead of standing wave exicitation, which allows a theoretical increase of power density by a factor √2. Theo theoretical basics as well as prototype of a travelling wave type piezoelectric transformer are presented.